2019
DOI: 10.18203/2320-1770.ijrcog20194902
|View full text |Cite
|
Sign up to set email alerts
|

Chronic uterine inversion associated with uterine leiomyoma misdiagnosed as cervical fibroid: a case report

Abstract: Chronic inversion of uterus is a rare clinical entity which is usually associated with obstetrics complication and rarely with gynaecological disorder like fibroid present at fundus of uterus. We here present a case of 40-year-old female P3L3 with chronic inversion of uterus with fundal fibroid which present with 3year history of abnormal vaginal bleeding. Ultrasonography and MRI revealed cervical fibroid. Due to AUB secondary to cervical fibroid decision of hysterectomy was taken. On laparotomy chronic uterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The occupying tumor appears similar to a cervical tumor in some cases of nonpuerperal uterine inversion. However, no case associated with cervical cancer has been reported previously [ 11 , 12 ]. To the best of our knowledge, this is the first reported case of nonpuerperal uterine inversion caused by cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occupying tumor appears similar to a cervical tumor in some cases of nonpuerperal uterine inversion. However, no case associated with cervical cancer has been reported previously [ 11 , 12 ]. To the best of our knowledge, this is the first reported case of nonpuerperal uterine inversion caused by cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our preoperative diagnosis was endometrial cancer because we considered that the tumor occupied the uterine corpus and that there are a few case reports of primary SCC of the endometrium [ 15 ]. In addition, some case reports suggested that nonpuerperal uterine inversion was wrongly attributed to the cervical tumor in the preoperative diagnosis [ 11 , 12 ]. An accurate preoperative diagnosis is significant because the treatment of cervical cancer is different from other cancers.…”
Section: Discussionmentioning
confidence: 99%